Ciclagem diuturna do carbono entre águas superficiais estuarinas e a baixa atmosfera em clima semiárido - Rio Jaguaribe (CE) - Silva, Agda Raquel Facundo da (2019)
The biological diel cycle and physical processes, among other factors, can affect the concentrations of dissolved carbon dioxide in the water and consequently the CO2 fluxes at the water-atmosphere interface in estuaries. Studies on the behaviour of estuaries in relation to CO2 emission or absorption are still scarce in semi-arid coastal regions. The present study was carried out in lower portion of the Jaguaribe river basin, which occupies half of the territory of the State of Ceará. Two Eulerian field data collection campaigns were conducted during dry season spring tides in October/2017 (33 hours) and in September/2018 (44 hours), using the direct method of measuring the partial pressure of carbon dioxide (pCO2). At the same time, temperature and salinity data were recorded, using a thermosalinometer and a portable multiparameter probe, the latter also measured dissolved oxygen concentrations. Water samples were collected hourly in duplicate for the analysis of chlorophyll a, total and dissolved phosphorus and total alkalinity. The high salinity values (above 39 in both campaigns) show the strong marine influence in the estuary and corroborate data on the negative water balance of the estuary. The estuary presented suboxic characteristics during the first sampling campaign with mean dissolved oxygen content (ẍ= 4.75 ± 0.35 mg.L-1) lower than that recommended by national legislation. The total alkalinity (AT) presented higher average values than those characteristic of seawater (ẍOut = 2569,61 ± 85,74 μmol.kg−1; ẍSet = 2609,25 ± 80,3 μmol.kg−1). The discrete pCO2 data showed a significant and inverse correlation with oxygen that, along with the assessment of the saturation states of these gases, indicated that respiration is a controlling process of pCO2 variability in the Jaguaribe estuary. Continuous pCO2 data were influenced by the period of the day and the state of the tide in both sampling campaigns. The Jaguaribe River Estuary acted as a continuous source of CO2 into the atmosphere with average fluxes calculated based on proposed equations for estuaries of 53.56 ± 24.72 mmol.m-2.d-1 and 70.13 ± 20, 75 mmol.m-2.d-1, respectively for the months of October and September. These fluxes were of the order of 31.32 ± 21.04 mmol.m-2.d-1 and 39.61 ± 20.84 mmol.m-2.d-1 when calculated with equations developed for oceans. Fluxes are believed to have been partly influenced by net primary productivity of the community, which indicated system heterotrophy during both sampling campaigns.